Moving towards a competence centre for geriatric medicine and care: Quality management and human resource management as major support factors. Issue 1 (March 2018) - Löffler, Kerstin; Goldgruber, Judith; Hartinger, Gerd
Abstract : Changed employment models, an ageing workforce and demands of new generations are challenging healthcare facilities to go down new paths. Never before have well-qualified staff been as highly sought after within the medical and nursing care sector as they are today. For many years, the Geriatric Health Care Centres of the city of Graz (GGZ)—a large regional health care provider with more than 650 staff across five locations—has focused a lot on the topic of competence management, facilitation of specialist and management careers in nursing and medicine as well as the optimal mix of skills and grades in staffing. In addition to competence management, quality management is another prerequisite for systematic staff development. The consistent path of quality management at GGZ has demonstrated for more than 15 years that the regular consideration of quality management systems supports the constant development of human resource management; additionally, it has also demonstrated that it leads to important certifications and prestigious prices: these include the KTQ award for Cooperation for Transparency and Quality in Health Care (Kooperation für Transparenz und Qualität im Gesundheitswesen) in 2010 and 2013, the Austrian Quality Award (Staatspreis Unternehmensqualität) in 2014, the European Quality Award from EFQM (European Foundation for Quality Management) in 2015 and runner-up for the Austrian award for the most family-friendly company (Staatspreis Familienfreundlichster Betrieb Österreichs) in 2014. Furthermore, the competitive edge is sustainably ensured. However, to remain competitive in the labour market and to satisfy the aforementioned requirements, skill-based teamwork and consideration of life-phase-orientation are keys to increase the job and life satisfaction of staff, especially for the mentally and physically draining work with elderly, chronically ill and dying patients. The facilitation of specialist and management careers and age-appropriate workplaces are in turn part of workplace health management of the company. Incorporating workplace health management into the corporate strategy allows health-related management decisions to be made. The integration of health-relevant agendas as strategic management instruments (e.g. the so-called balanced scorecard) is supported by the processes of quality management systems (e.g. EFQM). The strategic corporate objective of GGZ is to increase the health literacy of the population—and by doing so, also increases the health literacy of patients and residents. This kind of patient empowerment can be substantially supported by specially qualified, empathic staff with good social skills and a genuine interest in the elderly; this reinforces the high significance of professional human resource management.